Impact of time to first antimicrobial dose on length of stay and 30-day hospital readmission in patients with lower limb cellulitis. (June 2021) - Bishop, Jaclyn L.; Jones, Mark; Farquharson, James; Summerhayes, Kathrine; Tucker, Roxanne; Smith, Mary; Cowan, Raquel; Friedman, N. Deborah; Schulz, Thomas R.; Kong, David C.M.; Buising, Kirsty L.
Highlights: Time to first antimicrobial dose (TFAD) is important in some infections. The impact of TFAD on outcomes for cellulitis is not well studied. TFAD was observed not to impact acute length of stay in clinically stable patients. Taking time to confirm the diagnosis before prescribing antimicrobials seems acceptable. ABSTRACT: Objectives: There have been efforts to promote timely antimicrobial administration for patients with sepsis, but the importance for other infections is uncertain. This study analysed whether time to first antimicrobial dose (TFAD) in patients with lower limb cellulitis influenced outcome measures such as acute length of stay (LOS) in hospital and 30-day hospital readmission rates for cellulitis. Methods: Medical records of patients admitted with lower limb cellulitis or erysipelas over a 15-month period (1 May 2019 to 30 November 2019 and 1 March 2020 to 31 October 2020) were reviewed. Patients requiring intensive care unit (ICU) admission were excluded. The TFAD was the difference (in minutes) between the emergency department triage time and the time that the antimicrobial was first recorded as administered. Analysis included log-transformed linear regression (for LOS) and logistic regression (for 30-day readmission with cellulitis), controlling for confounders where possible. Results: The study included 282 patients with lower limb cellulitis. The median TFAD was 177 min (interquartile range, 98–290 min). Linear regression suggested a weak association between TFAD and LOS ( P = 0.05; adjusted R 2 = 0.01), which was non-significant after adjusting for confounders ( P = 0.18). There were too few patients readmitted within 30 days with cellulitis for meaningful analysis. Conclusion: After controlling for confounders, no association between increased TFAD and increased acute LOS was identified for patients with lower limb cellulitis who did not require ICU admission (i.e. without septic shock). Conclusions could not be made for 30-day readmission rates for cellulitis.